Respiratory questionnaire‐based analysis of awareness of COPD in a large multicenter rural population‐based study in India - Shital Patil; Rajesh Patil; Mukund Bhise; Anil Jadhav (Chronic Diseases and Translational Medicine, 2022)
Abstract Background Chronic obstructive pulmonary disease (COPD) is a more prevalent chronic lung disease with a significant health burden, and the majority of these cases receive inadequate treatment. Methods Prospective, observational, interview (questionnaire) based complete workup COPD study, screened 12,000 cases with chronic respiratory symptoms with cough, sputum production, and shortness of breath. A total of 6000 COPD cases were enrolled after the spirometry test. COPD cases were assessed as disease knowledge and methods of treatment offered by applying questionnaires to patients and treating physicians. Results In the present study, 3% of study cases were aware of their COPD illness, 54% were not having knowledge about the disease, and 43% cases were not accepting the COPD diagnosis (p < 0.0001). A total of 58% of cases received inhalation treatment as levosalbutamol monotherapy in 31% cases, levosalbutamol plus beclometasone in 18% cases, and formoterol plus budesonide or salmeterol plus fluticasone only in 9% of COPD cases (p < 0.0001). Total 42% cases received oral treatment as theophylline in 16% cases, salbutamol in 7% cases, oral steroids in 19% cases (p < 0.0001). Conclusion “Doctor–patient–drug trio” discordance clubbed as “difficult doctor, difficult patient, and difficult treatment” is a very crucial issue observed during diagnosis and management of COPD in peripheral settings in India.